Challenges to the Success of Commercial Organic Photovoltaic Products. Issue 18 (24th March 2021) - Moser, Maximilian; Wadsworth, Andrew; Gasparini, Nicola; McCulloch, Iain
Abstract: Recent advances in the development of organic photovoltaic (OPV) materials has led to significant improvements in device performance; now closing in on the 20% efficiency threshold. Despite these improvements in performance, the commercial viability of organic photovoltaic products remains elusive. In this perspective, the current limitations of high performing blends are uncovered, particularly focusing on the industrial upscaling considerations of these materials, such as synthetic scalability, active layer processing, and device stability. Moreover, a simplified metric, namely, the scalability factor (SF), is introduced to evaluate the scale‐up potential of specific OPV materials and blends thereof. Of the most popular molecular design strategies investigated in recent times, it is found that the use of Y‐series nonfullerene acceptors (NFAs) and synthetically simple materials, such as PTQ‐10 and ternary blends, are most effective at maximizing the efficiency without negatively impacting the SF. Furthermore, the improvements that are needed, in terms of device processability and stability, are considered for industrial scale‐up and final product application. Finally, an outlook of organic photovoltaics is provided both from a perspective of important research avenues and applications that can be exploited. Abstract : This perspective focuses on the commercial pathways that organic solar cell technologies have taken to date, and provides a personal outlook for their future contributions to the photovoltaics industry. In particular, the remaining challenges for the industrialization of organic photovoltaics, relating to the scalability of the active layer materials, industrially viable processing, and limited focus on device stability, are discussed.